MicroRNAs modulate neuroinflammation after intracerebral hemorrhage: Prospects for new therapy - Xia, Siqi; Zheng, Yonghe; Yan, Feng; Chen, Gao (Frontiers in Immunology, 2022)
Intracerebral hemorrhage (ICH) is the most common subtype of hemorrhagic stroke. After ICH, blood components extravasate from vessels into the brain, activating immune cells and causing them to release a series of inflammatory mediators. Immune cells, together with inflammatory mediators, lead to neuroinflammation in the perihematomal region and the whole brain, and neuroinflammation is closely related to secondary brain injury as well as functional recovery of the brain. Despite recent progress in understanding the pathophysiology of ICH, there is still no effective treatment for this disease. MicroRNAs (miRNAs) are non-coding RNAs 17–25 nucleotides in length that are generated naturally in the human body. They bind complementarily to messenger RNAs and suppress translation, thus regulating gene expression at the post-transcriptional level. They have been found to regulate the pathophysiological process of ICH, particularly the neuroinflammatory cascade. Multiple preclinical studies have shown that manipulating the expression and activity of miRNAs can modulate immune cell activities, influence neuroinflammatory responses, and ultimately affect neurological functions after ICH. This implicates the potentially crucial roles of miRNAs in post-ICH neuroinflammation and indicates the possibility of applying miRNA-based therapeutics for this disease. Thus, this review aims to address the pathophysiological roles and molecular underpinnings of miRNAs in the regulation of neuroinflammation after ICH. With a more sophisticated understanding of ICH and miRNAs, it is possible to translate these findings into new pharmacological therapies for ICH.